STUDENTS’ PERCEPTIONS ON THE USE OF GAMIFICATION APPROACH IN GRAMMAR CLASS - Nur Laily Lupita Sari; I’anatul Avifah (Indonesian Journal of Education (INJOE), 2023)
This study explores students' perceptions on the use of a gamification approach in grammar classes at Universitas Billfath, focusing on two English as a Foreign Language (EFL) classrooms— Basic English Grammar and Advanced English Grammar— comprising 36 participants. Employing a qualitative method with analytical descriptives, the research used a survey to assess students' views on the gamification approach in their respective grammar classes. The primary objective of this assessment was to comprehensively investigate the effective implementation of gamification in grammar classrooms, aiming to capitalize on its strengths and address its limitations to achieve the desired educational objectives. The data collection was accomplished through the distribution of questionnaires. Subsequently, the questionnaire responses were quantitatively analyzed and categorized based on specific themes to gain valuable insights into students' perceptions on the use of gamification in grammar classes.